1968
DOI: 10.1063/1.1655829
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Properties of Single Crystals of n- and p-Type Tungsten Diselenide (WSe2)

Abstract: The optical absorption, photoconductivity, contact photovoltage, electrical conductivity, and Hall coefficient of single crystals of WSe2 have been studied over the temperature range 77°–295°K. It was found that the forbidden energy gap Eg was 1.35 eV at 295°K and that the temperature dependence of Eg was given by dEg/dT=−4.6×10−4 eV/°K. The material as grown by iodine vapor transport in a sealed ampule is p-type with hole mobility μh∼80 cm2/V·sec and p∼1016/cc at 295°K. The carrier concentration could be redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(34 citation statements)
references
References 4 publications
3
31
0
Order By: Relevance
“…Additional evidence for hole localization is provided by the observed energy shift of the core levels of about 0.5 eV (see Fig. above), which is smaller than half of the band gap E g of WSe 2 (E g = 1.35 eV ), i.e., starting from a mid gap position of the Fermi level E F for undoped WSe 2 , this would indicate a pinning of E F above the valence band edge.…”
Section: Resultsmentioning
confidence: 88%
“…Additional evidence for hole localization is provided by the observed energy shift of the core levels of about 0.5 eV (see Fig. above), which is smaller than half of the band gap E g of WSe 2 (E g = 1.35 eV ), i.e., starting from a mid gap position of the Fermi level E F for undoped WSe 2 , this would indicate a pinning of E F above the valence band edge.…”
Section: Resultsmentioning
confidence: 88%
“…Similarly, the 3L WSe 2 FET also showed the p‐type doping characteristic with a higher current On/Off ratio of 400 (Figure S7D in SI). Since there are two kinds of WSe 2 single crystals, i.e., p‐type and n‐type, depending on the synthesis procedure,28, 56, 57 our electric results of WSe 2 FETs indicate that the p‐type single crystal of WSe 2 was used in this study.…”
Section: Resultsmentioning
confidence: 92%
“…From this point of view, source materials and the mineralizer can be regarded as the most decisive factors in the growth of TMD crystals. Thereafter, the reaction conditions could be optimized case by case, typically in an empirical way, and some representative reactions are summarized in Table 1 …”
Section: Cvt Based Synthesis Of 2d Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…Source materials and mineralizer are the decisive factors in CVT based synthesis of TMD crystal, and thus modulating the two factors can tune the features of resulting bulk TMD crystals. For example, for the synthesis of semiconducting WSe 2 , it was found that the mineralizer of Br 2 , SeCl 4 , or TeCl 4 selectively favors the formation of n‐type WSe 2 , while the mineralizer of I 2 yields its p‐type counterpart . In addition to the change of mineralizer, varying the ratio of source materials and the mineralizer is also a way to influence the features of the as‐synthesized TMD materials.…”
Section: Cvt Based Synthesis Of 2d Transition Metal Dichalcogenidesmentioning
confidence: 99%